Placebo Economics: A Systematic Review About the Economic Potential of Utilizing the Placebo Effect - Hamberger, Jens; Meissner, Karin; Hinterberger, Thilo; Loew, Thomas; Weimer, Katja (Frontiers in Psychiatry, 2019)
Background: Recent research shows that placebo mechanisms can be utilized in ethical and legal ways such as in open-label conditions, when patients know that they receive placebos, and through psychological interventions aiming to optimize patients’ expectations. Showing that placebo interventions are also cost-efficient could improve their acceptability. Objective: To review studies that performed health economic evaluations (HEE) of intentional placebo interventions, and to review studies that intentionally applied placebo interventions and reported outcomes eligible for HEE. Methods: Two systematic reviews of the literature were performed. For the first review, we searched Medline using “placebo” and MeSH Terms associated with HEE such as “costs”, “cost-benefit analyses”, and “economics”. Studies were eligible if they employed patients, applied placebo interventions, included an appropriate control group, and reported results of cost analyses. For the second review, we searched the Journal of Interdisciplinary Placebo Studies (JIPS) database and Medline using search terms for outcomes eligible for cost-utility analyses, such as “quality of life” or “quality-adjusted life years” (“QALY”). Risk of bias of all studies found was assessed according to the Cochrane Handbook, and a narrative synthesis of the results is provided. Results: The first search resulted in 1853 articles which were screened for eligibility. Two studies were found only in which costs or cost-effectiveness analysis were reported, but with medium to high risks of biases. The second search yielded 164 articles particularly from the JIPS database of which 11 studies met our search criteria: in six studies patients received placebo pills in open-label conditions, three studies investigated effects of patient-physician relationships, and two studies used psychological interventions to optimize treatment expectations, in patients with various diseases and disorders. These studies report outcomes potentially eligible for HEE when costs of interventions were known. Risks of biases were low to medium, but patients were not blinded to the conditions in most studies. Conclusions: The state of knowledge about HEE of placebo interventions is scarce. To gain more visibility and acceptability for placebo interventions, future studies should measure outcomes usable for HEE and costs of interventions, and HEE should be performed for existing studies if data are available.